2010
DOI: 10.1088/0004-637x/719/1/45
|View full text |Cite|
|
Sign up to set email alerts
|

THE ALLEN TELESCOPE ARRAY TWENTY-CENTIMETER SURVEY—A 690 DEG2, 12 EPOCH RADIO DATA SET. I. CATALOG AND LONG-DURATION TRANSIENT STATISTICS

Abstract: We present the Allen Telescope Array Twenty-centimeter Survey (ATATS), a multi-epoch (12 visits), 690 deg 2 radio image and catalog at 1.4 GHz. The survey is designed to detect rare, very bright transients as well as to verify the capabilities of the ATA to form large mosaics. The combined image using data from all 12 ATATS epochs has rms noise σ = 3.94 mJy beam −1 and dynamic range 180, with a circular beam of 150 FWHM. It contains 4408 sources to a limiting sensitivity of 5σ = 20 mJy beam −1 . We compare the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 33 publications
3
33
0
Order By: Relevance
“…Despite specific studies designed to search for OAs in X-ray surveys (Grindlay 1999;Greiner et al 2000), in optical surveys (Vreeswijk 2002;Rau et al 2006;Malacrino et al 2007;Rau et al 2007), and in the radio band (Levinson et al 2002;Gal-Yam et al 2006;Bannister et al 2011;Bell et al 2011;Bower & Saul 2011;Croft et al 2010;Frail et al 2012;Carilli et al 2003;Matsumura et al 2009;Lazio et al 2010), no OA have been conclusively detected so far.…”
Section: Introductionmentioning
confidence: 99%
“…Despite specific studies designed to search for OAs in X-ray surveys (Grindlay 1999;Greiner et al 2000), in optical surveys (Vreeswijk 2002;Rau et al 2006;Malacrino et al 2007;Rau et al 2007), and in the radio band (Levinson et al 2002;Gal-Yam et al 2006;Bannister et al 2011;Bell et al 2011;Bower & Saul 2011;Croft et al 2010;Frail et al 2012;Carilli et al 2003;Matsumura et al 2009;Lazio et al 2010), no OA have been conclusively detected so far.…”
Section: Introductionmentioning
confidence: 99%
“…In Croft et al (2010), hereafter Paper I, we introduced a 12-epoch survey undertaken with the Allen Telescope Array (ATA; Welch et al 2009), the ATA Twenty-centimeter Survey (ATATS), and compared the image and catalog made with data from all 12 epochs to the NRAO VLA Sky Survey (NVSS; Condon et al 1998), a survey also at 1.4 GHz (with 45 resolution, compared to the 150 resolution of our data) undertaken with the VLA between 1993 and 1997. Unfortunately, both the raw and reduced data for epoch ATA4 were subsequently lost due to two disk failures, so for this paper we created a new image and catalog made with data from the remaining 11 epochs (which we term the master mosaic and master catalog).…”
Section: Introductionmentioning
confidence: 99%
“…The sources were detected in a drift scan mode and have flux densities greater than 1 Jy, with typical timescales of minutes to days. (Note, however, the questions raised about these results by Croft et al 2010Croft et al , 2011, and the discussion about the resulting transient event rates by Ofek et al 2011. ) As briefly discussed earlier in Section 3.1, Bower et al (2007) reported the detection of 10 transient radio sources in archival VLA data at 4.8 and 8.4 GHz.…”
Section: Gigahertz Surveysmentioning
confidence: 99%